POLA TABUHAN TEBAH GENDANG DAYAK IBAN SEBARUK DI KECAMATAN SEKAYAM KABUPATEN SANGGAU - Harry Fandinus; Imam Ghozali; Asfar Muniir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe uniqueness Tebah Gendang of Iban Sebaruk Dayak tribe in Sekayam District Sanggau regency. This study aims to analyze the beats patterns and the technique of playing Tebah Gendang. This study was conducted using the descriptive-analytic method in the form of qualitative research. The approach used in conducting the study was musicology. The researcher acted as the research instrument. The data were gathered from the public figure in the community and the kendang craftsmen and players, of which they were collected using observation, interviews, and documentary study techniques. The data were validated by sources triangulation and technique triangulation and. were analyzed by adapting the technique from Miles and Huberman such as data reduction, data presentation, and verification. The findings show that there are eight patterns of tebah gendang beats; they are tebah pekak ayam, babi makan belaut, tungkat tebuh betung, pelebar, gendang nait, kuntau, ngajat and banong belit. In addition, there are two sounds produced (“dup” and “pak”), which were formed from being hit using the palm. This artistry is unique because it has a variety of different beat patterns with other musical instruments. Based on the results, it is necessary to study further to make it material in learning local musical instruments. Keywords: Tebah Gendang, Musicology, Dayak Iban Tribe of Sebaruk